Sumbangan kegiatan kokurikulum ke arah pencapaian matlamat pendidikan guru : satu kajian keberkesanan - Nordin, Mohamad Sahari; Hashim, Rosnani (Yayasan Takmir, 1998)
The importance of co-curricular activities with respect to meeting the goal of an educational institution has been a debatable issue. However, increasingly more studies have been conducted to investigate the matter. This study is one of such nature. It examines from students teachers perception, the effectiveness of major co-curricular activities in the Diploma of Education Programme's philosophy and objectives. The subjects of the study were student teachers from the 1994/95 academic session. The study employed a survey method using questionnaires and interviews. The result indicate that more than 90% of the respondents felt the halaqah (study circle) as effective in increasing their knowledge of Islam, in strengthening the Islamic brotherhood (ukhuwwah( and in providing an arena for exchange of ideas. They also felt strongly (about 80%) that it has helped hem to work together collectively (amal jama'iy) and raise their awareness on current issues. Similarly, the student teachers felt that the ta'aruf (students' orientation) programme was effective in introducing them to the Diploma of Education Programme, its philosophy and objectives, awareness of their mission, strengthening the Islami brotherhood and increasing their understanding of Islam.